Eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cell and preparation method of eutectic high-entropy alloy-based gas diffusion layer
By using eutectic high-entropy alloy AlFeCoCrNi2.1 material and SLM technology to prepare a three-dimensional lattice-like superstructure gas diffusion layer, the problems of insufficient catalyst performance and structural design in AEMWE water electrolysis technology were solved, realizing efficient and low-cost water electrolysis for hydrogen production.
Patent Information
- Application Number
- CN202511958958.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-01-23
- Estimated Expiration
- 2045-12-24
AI Technical Summary
In existing AEMWE water electrolysis technology, the catalyst performance is insufficient, the cost is high, and the stability is poor. The gas diffusion layer structure design cannot achieve an effective combination of catalytic activity and mechanical support, and traditional manufacturing methods are difficult to prepare high-performance GDL with complex structures.
A three-dimensional lattice-like superstructure gas diffusion layer was prepared using the eutectic high-entropy alloy AlFeCoCrNi2.1 through machine learning-aided design and selective laser melting (SLM) technology. Combined with heat treatment, the material and structure were integrated to optimize catalytic activity and mechanical stability.
The prepared eutectic high-entropy alloy-based gas diffusion layer exhibits high catalytic activity, excellent mechanical strength, and good mass transfer performance, significantly improving the efficiency and durability of hydrogen production through water electrolysis, reducing costs, and solving the problems of catalyst stability and limited mass transfer.
Smart Images

Figure CN121373468A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of hydrogen production by water electrolysis, and particularly relates to a eutectic high-entropy alloy-based gas diffusion layer for an AEMWE electrolytic cell and a preparation method thereof. BACKGROUND
[0002] Hydrogen energy is considered as an ideal green energy to replace fossil fuels due to its light weight, high heat value, and zero pollution. Among them, the water electrolysis hydrogen production technology is simple in process and pure in product, and can realize carbon cycle, which is an important way for clean production of ultra-pure hydrogen. The technology makes water decompose into hydrogen and oxygen on the electrode surface through electrochemical reaction by electric energy, including cathode hydrogen evolution reaction (HER) and anode oxygen evolution reaction (OER). According to the type of electrolyte, the water electrolysis hydrogen production is mainly divided into alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEM), solid oxide water electrolysis (SOEC), and anion exchange membrane water electrolysis (AEMWE). Among them, AEMWE combines the advantages of AWE and PEM, uses anion exchange membrane as solid electrolyte, and has low-cost catalyst compatibility and high-current density operation capability, which is a new type of water electrolysis technology with development potential.
[0003] Although the water electrolysis technology such as AEMWE has broad prospects, its large-scale application is still restricted by high cost, low efficiency and high energy consumption, and the insufficient performance of the catalyst is the core restricting factor. The electrolysis reaction is highly dependent on high-efficiency catalysts to reduce the overpotential and improve the energy conversion efficiency. At present, although the noble metal catalysts have excellent performance, their high cost and resource scarcity promote the research and development of high-performance and low-cost non-noble metal catalysts. Such catalysts need to be optimized in composition and designed in structure (such as porous, low-dimensional or heterogeneous structure) to expose more active sites and enhance mass transfer, so as to realize the catalytic activity and stability comparable to noble metals. However, excellent catalyst powders need to be loaded on a specific conductive substrate to form an effective electrode. Here, the gas diffusion layer (GDL) as a key component of the electrolytic cell has an important influence on the catalytic efficiency and system performance. A good GDL needs to have high conductivity, suitable pore structure and good hydrophobicity to realize efficient transmission of reaction gas, timely discharge of liquid water and electronic conduction, and at the same time provide stable support for the catalyst, so as to improve the reaction efficiency of three-phase interface and the overall durability. Therefore, the integrated and collaborative design of material innovation of catalyst and structure design of gas diffusion layer, rather than simple "coating" and "loading", becomes the key path to break through the bottleneck of existing technology and promote the water electrolysis hydrogen production technology to scale application.
[0004] Based on the above-mentioned design concept of "material-structure integration", high-entropy alloys (HEA) show great potential. Transition metals have potential in electrocatalysis, but single metals are not stable enough. Multi-metal alloys can optimize performance through synergistic effects, among which high-entropy alloys (HEA) are composed of more than five elements in near-equi-molar ratios, with four core effects of high entropy, lattice distortion, sluggish diffusion and cocktail, which can effectively suppress phase separation, promote electron transfer, enhance structural stability and synergistically optimize catalytic activity. In particular, eutectic high-entropy alloys (EHEA), as an important branch of HEA, have a lamellar or rod-shaped two-phase lamellar structure formed by eutectic reaction, which further introduces rich phase interfaces and grain boundaries on the basis of retaining the advantages of HEA. This microstructure not only provides a large number of high-activity interface sites for electrocatalytic processes, significantly enhancing the reaction kinetics of HER and OER, but also effectively disperses stress, suppresses element segregation and phase coarsening, thereby greatly improving the durability and stability of the material in harsh electrolytic environments.
[0005] In order to combine the excellent intrinsic properties of EHEA with the complex macrostructure required by GDL, Selective Laser Melting (SLM), an advanced additive manufacturing technology, provides an ideal technical approach. SLM has high precision molding capability and can directly manufacture porous, flow channel or grid structures with complex three-dimensional periodic arrangement, meeting the stringent requirements of GDL for precise pore design and gas / liquid transmission path. Although this process can suppress element segregation through extremely high cooling rates (up to 10 8 K / s) to form uniform and fine microstructure, thereby improving the structural integrity and conductivity of the material, it will also introduce significant residual stress, which needs to be eliminated through subsequent heat treatment. By flexibly adjusting process parameters such as laser power and scanning strategy, SLM can precisely control the porosity, pore morphology and surface properties of GDL, thereby optimizing the reaction gas phase transmission, liquid water discharge and electronic conduction capacity. In addition, SLM does not require molds and has the characteristics of nearly net shaping, which is particularly suitable for rapid manufacturing of customized and integrated GDL, providing a strong technical approach for the development of a new generation of high-performance and long-life electrolytic cell electrodes.
[0006] In summary, the SLM technology is used to prepare the EHEA-based GDL structure with excellent water electrolysis performance, and the key factors such as thermal stress and microstructure evolution generated in the SLM process need to be considered to directly affect the catalytic performance. Process parameters such as laser power and scanning speed directly affect the solidification behavior of the molten pool, element distribution and defect formation, and then regulate the phase composition, interface characteristics and catalytic activity of the alloy. Subsequent heat treatment can effectively relieve residual stress, promote phase stabilization and microstructure homogenization, and further improve the comprehensive stability and electrochemical performance of the EHEA-GDL. In addition, the SLM technology gives the GDL structure design great flexibility, enabling complex three-dimensional spatial configurations with multiple porosities; such structures not only expand the electrochemically active area, but also effectively optimize the reaction mass transfer, gas diffusion and electron transport path, thereby significantly enhancing the hydrogen / oxygen evolution reaction efficiency. Therefore, by synergistically optimizing the SLM process, post-processing and structure design, an EHEA-based GDL with high catalytic activity and good durability can be prepared, providing a material and structure integrated solution for promoting high-performance water electrolysis hydrogen production technology.
[0007] Through the above analysis, the problems and defects of the prior art are that: on the material, non-noble metals and high performance and high stability cannot be considered; on the structure, there is an interface problem between the catalytic layer and the diffusion layer; on the manufacturing, it is difficult to realize the synergistic control of complex structure and excellent material microstructure; and there is a lack of an overall solution that can integrate low-cost, high-stability catalytic materials and precisely controllable three-dimensional porous transport structures. SUMMARY
[0008] To overcome the problems in the related art, the present application discloses a eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cells and a preparation method, which uses machine learning to assist in designing material composition and macrostructure, uses SLM technology to realize integrated preparation of materials and structures, and finally optimizes the comprehensive performance through heat treatment process. The technical solution is as follows:
[0009] The present application is realized as follows: a preparation method of a eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cells, comprising the following steps:
[0010] S1, using a gas atomization method to prepare a eutectic high-entropy alloy spherical powder with a composition of AlFeCoCrNi 2.1 ;
[0011] S2, through the SLM process, a model with a three-dimensional crystal lattice superstructure is established under optimized parameters;
[0012] S3, using the SLM technology, the eutectic high-entropy alloy spherical powder is integrated and formed into a gas diffusion layer component according to the model under a protective atmosphere.
[0013] S4, heat treating the gas diffusion layer member, and then electrochemically de-alloying the gas diffusion layer member in an acidic solution to form a three-dimensional bi-continuous nanoporous structure on the surface.
[0014] In step S1, the preparation of the eutectic high-entropy alloy spherical powder includes:
[0015] After the metal raw materials with an atomic ratio of Al:Fe:Co:Cr:Ni = 1:1:1:1:2.1 are weighed, cleaned by alcohol ultrasonic and dried, the surface contaminants are removed;
[0016] The pretreated metal raw materials are placed in a vacuum induction melting furnace for vacuum induction melting, and the melting temperature is controlled at 150-300°C above the liquidus of the alloy, and the melting is repeated for 4-6 times;
[0017] The spherical alloy powder is prepared by high-pressure gas atomization method under the argon atmosphere of 2-8 MPa, and the eutectic high-entropy alloy spherical powder with a particle size of 15-53 μm is obtained by screening.
[0018] Further, before vacuum induction melting of the metal raw materials, the oxygen content in the furnace is reduced to 10 -2 Pa or below by vacuum-argon circulation treatment.
[0019] In step S2, the pseudo-lattice superstructure adopts a face-centered cubic, body-centered cubic or multi-phase inlaid composite form, the rod diameter is 100-500 μm, and the porosity is 50-80%.
[0020] In step S3, the eutectic high-entropy alloy spherical powder is integrated into a gas diffusion layer member according to the model, including:
[0021] A three-dimensional model of the pseudo-lattice structure is designed using CAD software, and converted into a standard triangulation language file;
[0022] According to the Z-axis height, surface roughness and minimum support structure requirements, the optimal manufacturing direction is adjusted, and the support structure is generated;
[0023] The model file is sliced into equal-thickness layers according to the set thickness, and the sliced data is transmitted to the SLM device;
[0024] The 304 stainless steel substrate is preheated, and the preheating temperature is controlled at 80-120°C, and then a layer of metal with a thickness of 20-50 μm is uniformly laid on the preheated substrate;
[0025] The high-energy density laser beam selectively melts the metal powder in the x-y plane according to the path planning data;
[0026] The powder spreading blade spreads a layer of metal powder on the finished layer, and the laser beam selectively melts according to the slice data of the next layer, and the powder spreading is repeated until the gas diffusion layer component is obtained.
[0027] Further, the substrate preheating temperature is 80-120 DEG C, the powder spreading thickness is 20-50 mu m, and the protective atmosphere is argon with oxygen content lower than 100 ppm;
[0028] The process parameter range of the selective laser melting technology is as follows: laser power is 100-350 W, scanning speed is 600-1000 mm / s, scanning interval is 0.06-0.1 mm, and layer thickness is 20-60 mu m;
[0029] The overall size of the gas diffusion layer component is 18 mm*5 mm*3 mm and 20 mm*20 mm*20 mm.
[0030] In step S4, the heat treatment is carried out under vacuum, and the temperature is raised to 600-1100 DEG C at a rate of 5 DEG C / min, and the temperature is kept for 1-6 h; after the temperature keeping, the temperature is lowered to below 300 DEG C at a rate of 2 DEG C / min, and the furnace is cooled to room temperature;
[0031] The electrochemical dealloying treatment adopts a double electrode, and a constant voltage of 4 V is applied in a 0.5 mol / L sulfuric acid solution for 60 min.
[0032] Another purpose of the application is to provide a eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cells, which is prepared by the preparation method of the eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cells, and the material of the gas diffusion layer is AlFeCoCrNi 2.1 Eutectic high-entropy alloy, and has a three-dimensional crystal lattice macroscopic pore structure and a three-dimensional double-continuous nano-porous structure covering the surface of the macroscopic structure skeleton.
[0033] Further, in a 1.0M KOH electrolyte, at least one of the following performance indicators is met:
[0034] The hydrogen evolution reaction is at a current density of 50 mA cm -2 The overpotential is less than or equal to 150 mV;
[0035] The oxygen evolution reaction is at a current density of 50 mA cm -2 The overpotential is less than or equal to 300 mV;
[0036] The Tafel slopes of the hydrogen evolution reaction and the oxygen evolution reaction are less than 180 mV / dec and 110 mV / dec, respectively;
[0037] The hydrogen evolution reaction is at a current density of 50 mA cm -2The activity decay rates of the hydrogen evolution reaction and the oxygen evolution reaction are not more than 5% after continuous operation for 120 hours at the current density.
[0038] Further, the material has a multi-level pore structure, and the compressive yield strength is 800-2000 MPa, the compressive strength is 1000-3200 MPa, and the strain rate is 20-35%
[0039] In combination with all the above technical solutions, the present application has the following beneficial effects:
[0040] First, the present application designs a eutectic high-entropy alloy with the composition of AlFeCoCrNi 2.1 by machine learning, and integrates a gas diffusion layer with a three-dimensional crystal lattice superstructure based on selective laser melting (SLM) technology. The present application uses a gas atomization method to prepare spherical alloy powder; a component with a multi-level pore is formed under optimized parameters by an SLM process; and then heat treatment is performed to eliminate residual stress and optimize the microstructure.
[0041] The present application specifically relates to a eutectic high-entropy alloy (EHEA) catalytic material composed of Al, Fe, Co, Cr and Ni elements, which has a chemical composition of AlFeCoCrNi 2.1 . The present application designs a variety of superstructures with macro-scale pore structures by means of machine learning, and realizes the preparation of the material superstructure by selective laser melting (SLM) technology. The present application optimizes the thermal stress and microstructure morphology generated in the SLM forming process through a heat treatment process, and finally applies the optimized new material and new structure to the gas diffusion layer of an AEMWE electrolytic cell to realize the integrated integration of mechanical support, gas-liquid diffusion and catalytic activity, which belongs to an innovative material-structure-function collaborative design method.
[0042] The eutectic high-entropy alloy-based gas diffusion layer prepared by the present application has high catalytic activity, excellent mechanical strength and good mass transfer performance, realizes the integrated integration of hydrogen evolution / oxygen evolution reaction sites and gas transport channels, significantly improves the efficiency and durability of the AEMWE electrolytic cell, and provides an effective solution to the problems of high cost, poor stability and limited mass transfer of water electrolysis catalysts.
[0043] Second, the preparation process of the application is innovative and the organizational performance is improved: the gas diffusion layer (GDL) is prepared by selective laser melting (SLM) technology, which overcomes the defects such as composition segregation, coarse structure and cracks easily produced by traditional casting method. By optimizing the process parameters such as laser power and scanning speed, the formed part with a density higher than 99.5% is obtained, which ensures the structural integrity and conductivity. The SLM rapid melting process significantly refines the grains, increases the number of grain boundaries as efficient catalytic sites, and thus improves the intrinsic catalytic activity. The subsequent heat treatment process effectively eliminates the residual tensile stress generated during the forming process, greatly enhances the structural stability and long-term service life of the electrode, and avoids stress corrosion failure.
[0044] The mechanical structure of the application is excellent: EHEA itself has high strength and high hardness, which provides a solid foundation for GDL. The integrated structure realized by SLM technology fundamentally avoids the problem of easy peeling and pulverization of traditional catalytic coating. This structure has very high compression resistance, not only can withstand the huge fastening force during electrolytic cell assembly, but also can resist fluid erosion in long-term operation, effectively preventing performance degradation due to structural collapse, thereby ensuring the long-term shape stability and service life of the electrode.
[0045] The application has high structural design freedom and improves mass transfer efficiency: thanks to the characteristics of SLM technology such as no mold and free forming, the application successfully prepares a gas diffusion layer electrode with a three-dimensional porous lattice structure. This design greatly increases the specific surface area of the electrode, exposing more catalytically active sites. At the same time, the interconnected pore structure significantly optimizes the mass transfer efficiency, promoting the rapid escape of reaction bubbles and smooth supply of electrolyte, effectively avoiding the shielding of active sites by bubbles, thereby exhibiting lower overpotential and Tafel slope at high current density, and significantly improving the overall catalytic efficiency.
[0046] The process chain system of the application is optimized and the reproducibility is guaranteed: the application provides a complete and systematic process scheme from high-quality spherical powder preparation (gas atomization method) to lattice-like superstructure establishment, SLM forming process window, post-processing heat treatment system, and performance evaluation. The parameter range of each step is optimized and verified to ensure the repeatability of the preparation process and the consistency of the performance of the final product, laying a solid foundation for industrial application.
[0047] In summary, the application combines novel high-entropy alloys, advanced SLM additive manufacturing technology, structural design concepts, and systematic post-processing processes to successfully create a new type of EHEA-based gas diffusion layer with excellent performance, controllable structure, and reliable preparation, solving multiple pain points in traditional materials and processes and promoting the development of high-performance electrolytic water devices.
[0048] Third, the present application directly faces the huge market of green hydrogen energy, by adopting non-noble metal eutectic high-entropy alloy material, getting rid of the dependence on noble metal catalyst, greatly reducing the cost of raw materials and manufacturing. The integrated structure design further improves the electrode performance, reduces the energy consumption, prolongs the service life, and has higher economy in the whole life cycle. At the same time, the SLM additive manufacturing process is introduced, which opens up a new path for the development of the next generation of high-performance, customized electrolytic cell, and has great potential for technology spillover.
[0049] Unlike the current widely used "inert matrix + coated catalyst" traditional mode, the present application first forms a gas diffusion layer with three-dimensional ordered pores by selective laser melting technology through eutectic high-entropy alloy with intrinsic catalytic activity, realizes the integration of mechanical structure, catalytic activity and mass transfer function, and fills the technical gap in the field of integrated design and manufacturing from materials to structure.
[0050] Traditional non-noble metal catalysts face problems such as insufficient activity and stability, dependence on binder, and easy falling off. The present application realizes high catalytic activity, excellent structural stability and optimized mass transfer path of the electrode without using noble metal through the synergistic innovation of material and manufacturing process, and solves the long-standing technical bottleneck in this field. The present application breaks through the cognition that "SLM formed parts are not suitable for electrocatalysis due to many defects", through machine learning and heat treatment optimization, converts rapid solidification into structural advantages, and obtains high-density active interface; the present application breaks the one-sided view that "high-entropy alloy multi-element leads to dilution of active sites or formation of inert layer", through precise eutectic composition design and process control, using the synergistic effect of phase interface and active surface layer, and realizing excellent hydrogen evolution and oxygen evolution performance. BRIEF DESCRIPTION OF DRAWINGS
[0051] The accompanying drawings, which are incorporated into and form part of the specification, illustrate embodiments consistent with the present disclosure and, together with the specification, serve to explain the principles of the present disclosure;
[0052] Figure 1 is a preparation method flowchart of the eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cell provided by the embodiments of the present application; Figure 2 (a) is a schematic diagram of a crystal lattice structure sample prepared by light-cured 3D printing provided by Example 1, Figure 2 (b) is a schematic diagram of a crystal lattice structure sample prepared by light-cured 3D printing provided by Example 2, Figure 2 (c) is a schematic diagram of a crystal lattice structure sample prepared by light-cured 3D printing provided by Example 3, and Figure 2 (d) is a schematic diagram of a crystal lattice structure sample prepared by light-cured 3D printing provided by Example 4; Figure 3(a) is a scanning electron microscope image of the multi-level nanoporous structure of the eutectic high-entropy alloy prepared by the heat treatment assisted SLM of Example 1, Figure 3(b) is a scanning electron microscope image of the multi-level nanoporous structure of the eutectic high-entropy alloy prepared by the heat treatment assisted SLM of Example 2, Figure 3(c) is a scanning electron microscope image of the multi-level nanoporous structure of the eutectic high-entropy alloy prepared by the heat treatment assisted SLM of Example 3, and Figure 3(d) is a scanning electron microscope image of the multi-level nanoporous structure of the eutectic high-entropy alloy prepared by the heat treatment assisted SLM of Example 4; Figure 4(a) is a stress-strain curve of the compressive mechanical property of Example 1, Figure 4(b) is a stress-strain curve of the compressive mechanical property of Example 2, Figure 4(c) is a stress-strain curve of the compressive mechanical property of Example 3, and Figure 4(d) is a stress-strain curve of the compressive mechanical property of Example 4; Figure 5(a) is a polarization curve of the HER of the water electrolysis performance test result of Example 1, Figure 5(b) is a Tafel slope corresponding to the HER of the water electrolysis performance test result of Example 1, Figure 5(c) is a stability test diagram of the HER of the water electrolysis performance test result of Example 1 at 50 mA cm -2 Figure 5(d) is a polarization curve of the OER of the water electrolysis performance test result of Example 1, Figure 5(e) is a Tafel slope corresponding to the OER of the water electrolysis performance test result of Example 1, and Figure 5(f) is a stability test diagram of the OER of the water electrolysis performance test result of Example 1 at 50 mA cm -2 Figure 5(f) is a stability test diagram of the OER of the water electrolysis performance test result of Example 1 at 50 mA cm Figure 6(a) is a polarization curve of the HER of the water electrolysis performance test result of Example 2, Figure 6(b) is a Tafel slope corresponding to the HER of the water electrolysis performance test result of Example 2, Figure 6(c) is a stability test diagram of the HER of the water electrolysis performance test result of Example 2 at 50 mA cm -2 Figure 6(d) is a polarization curve of the OER of the water electrolysis performance test result of Example 2, Figure 6(e) is a Tafel slope corresponding to the OER of the water electrolysis performance test result of Example 2, and Figure 6(f) is a stability test diagram of the OER of the water electrolysis performance test result of Example 2 at 50 mA cm -2 Figure 6(f) is a stability test diagram of the OER of the water electrolysis performance test result of Example 2 at 50 mA cm Figure 7(a) is a polarization curve of the HER of the water electrolysis performance test result of Example 3, Figure 7(b) is a Tafel slope corresponding to the HER of the water electrolysis performance test result of Example 3, Figure 7(c) is a stability test diagram of the HER of the water electrolysis performance test result of Example 3 at 50 mA cm -2Figure 7 (d) is a polarization curve diagram of the OER of the electrolytic water performance test results provided by Example 3; Figure 7 (e) is a Tafel slope diagram corresponding to the OER of the electrolytic water performance test results provided by Example 3; Figure 7 (f) is a Nyquist diagram of the OER of the electrolytic water performance test results provided by Example 3 at 50 mA cm -2 Figure 7 (d) is a polarization curve diagram of the OER of the electrolytic water performance test results provided by Example 3; Figure 7 (e) is a Tafel slope diagram corresponding to the OER of the electrolytic water performance test results provided by Example 3; Figure 7 (f) is a Nyquist diagram of the OER of the electrolytic water performance test results provided by Example 3 at 50 mA cm Figure 8 (a) is a polarization curve diagram of the HER of the electrolytic water performance test results provided by Example 4; Figure 8 (b) is a Tafel slope diagram corresponding to the HER of the electrolytic water performance test results provided by Example 4; Figure 8 (c) is a Nyquist diagram of the HER of the electrolytic water performance test results provided by Example 4 at 50 mA cm -2 Figure 8 (d) is a polarization curve diagram of the OER of the electrolytic water performance test results provided by Example 4; Figure 8 (e) is a Tafel slope diagram corresponding to the OER of the electrolytic water performance test results provided by Example 4; Figure 8 (f) is a Nyquist diagram of the OER of the electrolytic water performance test results provided by Example 4 at 50 mA cm -2 Figure 8 (d) is a polarization curve diagram of the OER of the electrolytic water performance test results provided by Example 4; Figure 8 (e) is a Tafel slope diagram corresponding to the OER of the electrolytic water performance test results provided by Example 4; Figure 8 (f) is a Nyquist diagram of the OER of the electrolytic water performance test results provided by Example 4 at 50 mA cm DETAILED DESCRIPTION
[0053] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application will be described in detail below with reference to the accompanying drawings. In the following description, a large number of specific details are set forth in order to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without departing from the scope of the present application, so the present application is not limited to the specific implementation disclosed below.
[0054] The innovation of the present application lies in:
[0055] (1) Material system innovation: AlFeCoCrNi 2.1 As a basic material, the eutectic high-entropy alloy has a unique dual-phase lamellar structure, which not only maintains the synergistic effect of multiple elements of high-entropy alloys, but also has a large number of active sites on the phase interface, realizing the high-efficiency intrinsic catalytic activity of the material itself.
[0056] (2) Structural design innovation: Through machine learning assisted design, a superstructure gas diffusion layer with three-dimensional ordered pores is constructed, realizing accurate control of pore size, porosity and pore morphology, and optimizing the gas-liquid transmission path and electronic conduction network.
[0057] (3) Preparation process innovation: Selective laser melting technology is applied to the superstructure forming of the material, and through the optimization of the process parameter combination and the unique heat treatment system, the forming stress is effectively eliminated and the microstructure is refined, realizing high-precision and high-performance integrated manufacturing.
[0058] (4) Function integration innovation: Breakthrough the traditional "matrix + coating" electrode construction mode, realize the integration of mechanical support, gas-liquid transport and catalytic activity of gas diffusion layer, fundamentally solve the inherent problems such as easy falling off of catalytic layer and large interface resistance.
[0059] (5) Design method innovation: Establish a complete technical chain from material calculation, structure optimization, forming process to post-processing, form a "material-structure-function" collaborative design system solution, and provide a new paradigm for the development of high-performance electrolytic water electrode.
[0060] These innovations together constitute a complete technical system, making the prepared gas diffusion layer show significant advantages in catalytic activity, structural stability and mass transfer efficiency, and providing a feasible technical path for the performance improvement of AEMWE electrolytic cell.
[0061] Example 1, as shown in Figure 1 The preparation method of the eutectic high-entropy alloy-based gas diffusion layer for the AEMWE electrolytic cell provided by the embodiment of the application comprises the following steps:
[0062] S1, using a gas atomization method to prepare a eutectic high-entropy alloy spherical powder with a composition of AlFeCoCrNi 2.1 ;
[0063] S2, establishing a model with a three-dimensional crystal lattice superstructure under optimized parameters through an SLM process;
[0064] S3, using a selective laser melting technology to integrate and form the eutectic high-entropy alloy spherical powder into a gas diffusion layer component according to the model under a protective atmosphere;
[0065] S4, performing heat treatment on the gas diffusion layer component, and then performing electrochemical dealloying treatment on the gas diffusion layer component in an acidic solution to form a three-dimensional bicontinuous nanoporous structure on the surface.
[0066] 1. Preparation of metal powder
[0067] (1) Selecting block-shaped high-purity metal raw materials Al, Fe, Co, Cr and Ni with a purity of not less than 99.95%, and accurately weighing according to the atomic ratio Al:Fe:Co:Cr:Ni=1:1:1:1:2.1.
[0068] (2) Put the weighed metal raw materials into a beaker containing alcohol, and place it in an ultrasonic cleaner for 15 minutes to remove surface grease and oxides, and then dry it in a 80°C vacuum drying box for 2 hours.
[0069] (3) The cleaned and dried raw materials were loaded into a graphite crucible of a vacuum induction melting furnace. The melting chamber was vacuumed to 5x10 -3 Pa, and then high-purity argon gas (purity 99.999%) was filled to -0.05 MPa. This vacuuming-argon filling process was repeated 3 times to ensure that the oxygen content in the furnace was lower than 10 -2 Pa. Subsequently, melting was performed, with the melting temperature controlled at 1600°C (about 200°C higher than the estimated liquidus of the alloy), and the temperature was maintained for 10 minutes and uniform composition was achieved by electromagnetic stirring. To obtain a highly uniform alloy ingot, the above melting process was repeated 5 times.
[0070] (4) Spherical alloy powder was prepared by high-pressure gas atomization. After remelting of the alloy ingot, the molten metal stream was guided to the atomization nozzle through a flow guide pipe, and was broken and atomized into fine droplets under the flow of 6 MPa superhigh pressure argon gas. This high pressure condition is suitable for SLM process with strict requirements on powder sphericity and low oxygen content, and can effectively reduce the spatter and un-melted defects in the printing process.
[0071] (5) The atomized powder was cooled in an inert atmosphere protection collection tank. Then, the powder was sieved in an argon-protected glove box using a standard vibration sieve machine, and the powder with a particle size range of 15-53 μm was selected for SLM printing. This particle size range is an optimized selection: too fine particle size leads to poor flowability, uneven powder laying and increased oxygen content; too coarse particle size affects the melting effect and the surface quality of the formed part.
[0072] (6) The sieved powder was characterized: scanning electron microscope (SEM) observation showed that the powder was regular spherical with few satellite balls; the average particle size (D50) measured by a laser particle size analyzer was 38 μm; the flow time measured by a Hall flowmeter was 55 s / 50 g, showing good flowability, which is crucial for achieving thin, uniform and stable powder laying in the SLM process, and is a prerequisite for ensuring the consistency and high precision of the printed structure; the energy dispersive spectroscopy (EDS) results showed that the element content was basically consistent with the designed composition AlFeCoCrNi 2.1 , proving the effectiveness of the previous melting and atomization process and ensuring the accuracy of the chemical composition of the subsequent SLM formed part.
[0073] 2. Design and modeling of quasi-lattice superstructure
[0074] A biomimetic three-dimensional porous structure model based on a body-centered cubic (BCC) lattice was established using computer-aided design software. Key geometric parameters were set as follows: lattice rod diameter 300 μm, unit cell size 1.5 mm × 1.5 mm × 1.5 mm, and theoretical porosity 70%. The three-dimensional model was exported as an STL file, and a preliminary prototype was verified using photopolymerization 3D printing technology with resin material, confirming the feasibility and accuracy of the structural design, as shown in Figure 2(a). This step solved the technical problems of the traditional GDL structure being singular and having random and uncontrollable pore distribution. Through lattice-like design, precise programming of porosity, pore size, and shape was achieved, creating ideal three-dimensional channels for the rapid and orderly transport of reactants and products, while also providing a large loading area and stable mechanical support for the catalyst.
[0075] 3. SLM printing
[0076] (1) Import the BCC pseudo-lattice STL model designed above into the processing software of the SLM device (e.g., EOS M290).
[0077] (2) Place the model in the forming chamber along the Z-axis to minimize the support structure and ensure a high printing success rate. The software automatically generates the necessary supports.
[0078] (3) Slice the model and set the layer thickness to 30μm.
[0079] (4) Select a sandblasted 304 stainless steel substrate and preheat it to 100°C. Substrate preheating can effectively reduce the temperature gradient during the printing process, which is one of the key measures to control the warping deformation and residual stress of the formed parts. Use recycled AlFeCoCrNi 2.1 Alloy powder is used as raw material to lay a 30μm thick powder layer on the substrate.
[0080] (5) Select parameter combination #4 in Table 1 as the optimized process: laser power 150W, scanning speed 850mm / s -1 The scanning spacing was 0.07 mm, the layer thickness was 30 μm, and the laser scanning direction of adjacent layers was rotated by 67°. This parameter combination was optimized for the characteristics of AlFeCoCrNi2.1EHEA material, aiming to achieve a balance between the "keyhole" effect and the "conductive" melting mode. This ensures complete melting and densification of the powder while avoiding defects such as porosity and spheroidization caused by excessive energy input. The 67° scanning rotation strategy between layers helps to disperse heat accumulation, refine grains, and reduce anisotropy.
[0081] (6) In the high-purity argon protective atmosphere with the oxygen content strictly controlled at <100 ppm, the SLM equipment according to the set path, layer by layer, powder laying, selective melting, and cyclic reciprocating, finally integrally forms multiple gas diffusion layer samples with BCC paracrystalline structure. The overall size of the sample is 18 mm x 5 mm x 3 mm and 20 mm x 20 mm x 20 mm. The SLM technology solves the problem that the traditional processing method (such as sintering and pressing) cannot manufacture complex three-dimensional integrated GDL, realizes the integrated manufacturing of “material-structure-function”, and avoids the problem of weak interfacial bonding force caused by the mismatch of the thermal expansion coefficient between the catalyst coating and the substrate.
[0082] Table 1 SLM process parameter screening experiment
[0083] 4. Post-processing stage
[0084] (1) The paracrystalline GDL 18 mm x 5 mm x 0.5 mm sample is cut from the SLM formed substrate.
[0085] (2) Select 3# parameter combination in Table 2 for heat treatment: heat treatment temperature 800℃, heating rate 5℃ / min -1 , holding time 4 hours, then slowly cool to below 300℃ at a rate of 2℃ / min -1 , and finally cool to room temperature with the furnace. This heat treatment system is specially designed for SLM formed EHEA-GDL: the temperature of 800℃ is sufficient to drive atomic diffusion, effectively eliminate the residual stress of up to 165 MPa (64% reduction) accumulated in the SLM process, while inhibiting the coarsening of eutectic structure and promoting the formation of stable dual-phase structure. The slow heating and cooling rate is aimed at avoiding the introduction of new thermal stress, ensuring the dimensional stability and structural integrity of the material. This step solves the long-term service failure risk caused by the large internal stress and metastable structure of SLM parts, significantly improves the durability of GDL under the dynamic operating conditions of electrolytic cell.
[0086] Table 2 Heat treatment process parameter screening experiment
[0087] 5. Performance characterization and test results
[0088] (1) Residual stress: the XRD method measures that the surface residual stress of SLM state is 165 MPa (tensile stress), and the surface residual stress after heat treatment is 59.5 MPa (tensile stress), which is reduced by 64%. The large reduction of residual stress directly improves the fatigue resistance and stress corrosion cracking resistance of GDL, which is crucial for maintaining the structural stability in the frequently started and stopped electrolytic cell environment.
[0089] (2) The prepared GDL structure (sample size is 20 mm x 20 mm x 20 mm) is subjected to compression mechanical property evaluation, and the specific steps are as follows:
[0090] The heat-treated lattice-imitated GDL structure is subjected to quasi-static uniaxial compression test (strain rate is 1 x 10 -4 s -1 ) on a universal testing machine. The structure exhibits excellent mechanical properties, the compression yield strength reaches 1071 MPa, the compression strength is as high as 1522 MPa, and collapse does not occur at 30% strain, as shown in FIG. 4 (a), exhibiting good plasticity and energy absorption capacity. This performance shows that the GDL not only meets the requirement of the huge compressive stress generated by bolt fastening during electrolytic cell assembly, avoids structure collapse, but also maintains the integrity of the form under running vibration or accidental impact, solving the technical problems of insufficient mechanical strength of traditional porous metal GDL or carbon-based GDL and easy damage during assembly and operation.
[0091] (3) Electrolytic water performance:
[0092] The SLM printed alloy block is made into a sample with a sample size of 18 mm x 5 mm x 0.5 mm. In order to construct a high specific surface area nano-porous structure on the surface to further improve the catalytic activity, the sample is subjected to electrochemical dealloying treatment, the principle of which is to selectively corrode the active metal elements (such as Al) in the alloy, thereby leaving a three-dimensional double-continuous nano-porous skeleton rich in transition metals (Fe, Co, Cr, Ni). A double electrode is used for electrochemical dealloying, the working electrode: test sample; the counter electrode: carbon rod; the dealloying solution: 0.5 mol L -1 of sulfuric acid (H2SO4). The software CHI760e is used, and the parameters are set: constant voltage 4V for electrochemical dealloying, and the dealloying experiment is carried out for 60 minutes. The morphology after dealloying is shown in FIG. 3 (a). Micro-nano scale pores are successfully introduced on the surface of the macro lattice-imitated structure, forming a unique "macro-micro-nano" multi-level pore structure, which greatly increases the electrochemical active area. In a 1.0M KOH electrolyte, a standard three-electrode system is used for testing.
[0093] 1) Hydrogen evolution reaction performance:
[0094] a. Polarization curve: as shown in FIG. 5 (a), the overpotential (η -2 ) at a current density of 50 mA cm 50 -1 is 140 mV, which is much lower than the target of the application (≤150 mV).
[0095] b. The Tafel slope is 154.3 mV dec -1 , as shown in FIG. 5 (b), indicating that the HER reaction kinetics is rapid.
[0096] c. Stability: As shown in Figure 5 (c), the activity decay rate is about 3.8% after continuous electrolysis for 120 hours at a constant current density of 50 mA cm -2 , which demonstrates excellent long-term stability. This solves the pain point of non-noble metal catalysts in alkaline HER, which generally have poor stability, thanks to the excellent corrosion resistance of EHEA itself and the stable nanoskeleton formed after dealloying.
[0097] 2) Oxygen evolution reaction performance:
[0098] a. Polarization curve: As shown in Figure 5 (d), the overpotential (η -2 ) measured at 50 mA cm 50 current density is 279 mV, which is better than the target of the invention (≤ 300 mV).
[0099] b. Tafel slope is 69.9 mV dec -1 , as shown in Figure 5 (e), indicating excellent OER reaction kinetics.
[0100] c. Stability: As shown in Figure 5 (f), the activity decay rate is about 2.8% after continuous operation for 120 hours at a large current density of 50 mA cm -2 , which meets the stability requirement. This proves that the material also has excellent anti-passivation and anti-dissolution ability in harsh OER environment (high potential, strong oxidation), realizing the dual-function efficient catalysis of HER and OER.
[0101] This embodiment is aimed at industrial electrolytic cells with strict requirements on mechanical strength and long-term stability. By using a body-centered cubic (BCC) lattice (rod diameter 300 μm), a stable mechanical skeleton is constructed; and by using a medium-temperature heat treatment system at 800 ℃, 64% of the residual stress is effectively eliminated, while the eutectic structure is precisely stabilized and its excessive coarsening is inhibited, perfectly balancing stress relief and mechanical property retention. Its compression yield strength as high as 1071 MPa successfully solves the problem that traditional porous electrodes (such as sintered metal or carbon paper) are easily crushed under the pressure of tens of megapascal bolts, leading to failure of the pore structure and a sharp decline in mass transfer performance. This GDL provides excellent long-term dimensional stability and operational safety assurance for harsh industrial working conditions with frequent start-stop and load fluctuations.
[0102] In embodiment 2, the preparation method of the eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cells provided by the embodiment of the application comprises the following steps:
[0103] 1. Preparation of metal powder
[0104] (1) The block-shaped high-purity metal raw materials Al, Fe, Co, Cr and Ni with a purity of not less than 99.95% are accurately weighed according to the atomic ratio Al:Fe:Co:Cr:Ni=1:1:1:1:2.1.
[0105] (2) The weighed metal raw materials are placed in a beaker containing alcohol and cleaned in an ultrasonic cleaning machine for 15 minutes to remove surface grease and oxides, and then dried in a vacuum drying oven at 80°C for 2 hours.
[0106] (3) The cleaned and dried raw materials are loaded into a graphite crucible of a vacuum induction melting furnace. The melting chamber is vacuumed to 5×10 -3 Pa, and then high-purity argon (purity 99.999%) is filled to-0.05 MPa. This vacuuming-argon filling process is repeated 3 times to ensure that the oxygen content in the furnace is lower than 10 -2 Pa. Then, melting is carried out, and the melting temperature is controlled at 1600°C (about 200°C higher than the estimated liquidus of the alloy), and the composition is uniformly maintained for 10 minutes by electromagnetic stirring. In order to obtain a highly uniform alloy ingot, the above melting process is repeated 5 times.
[0107] (4) The spherical alloy powder is prepared by high-pressure gas atomization. After the alloy ingot is remelted, the molten metal liquid is guided through a flow guide tube to the atomizing nozzle, and is broken and atomized into fine droplets under the action of 6 MPa ultra-high pressure argon gas flow.
[0108] (5) The atomized powder is cooled in an inert atmosphere protection collection tank. Then, the powder is sieved in an argon protection glove box using a standard vibration sieve machine, and the powder with a particle size of 15-53 μm is selected for SLM printing.
[0109] (6) The sieved powder is characterized: scanning electron microscope (SEM) observation shows that the powder is regular spherical with few satellite balls; the average particle size (D50) measured by a laser particle size analyzer is 38 μm; the flow time measured by a Hall flowmeter is 55 s / 50 g, showing good flowability; the energy spectrum analysis (EDS) results show that the content of each element is basically consistent with the designed composition AlFeCoCrNi 2.1 .
[0110] 2. Design and modeling of quasi-lattice superstructure
[0111] A three-dimensional (3D) model of a biomimetic porous structure based on face-centered cubic (FCC) lattice was established using computer-aided design software. The key geometric parameters were set as follows: lattice rod diameter of 200 pm, unit size of 1.2 mm x 1.2 mm x 1.2 mm, and theoretical porosity of 65%. The 3D model was exported as an STL file, and a preliminary prototype was verified using resin material by means of light-curing 3D printing technology, confirming the feasibility and accuracy of the structure design, as shown in Fig. 2(b).
[0112] 3. SLM printing forming
[0113] (1) The FCC imitation lattice STL model designed above was imported into the processing software of an SLM device (e.g., EOS M290).
[0114] (2) The model was placed in the forming cabin along the Z-axis direction to minimize the support structure and ensure the success rate of printing. The software automatically generated the necessary support.
[0115] (3) The model was sliced, and the layer thickness was set to 40 pm.
[0116] (4) A sandblasted 304 stainless steel substrate was selected and preheated to 90 °C. The recovered AlFeCoCrNi 2.1 alloy powder described above was used as raw material to lay a 40 pm thick powder layer on the substrate.
[0117] (5) The 6# parameter combination in Table 1 was selected as the optimized process: laser power 200 W, scanning speed 600 mm s -1 , scanning pitch 0.08 mm, layer thickness 40 pm, and adjacent layer laser scanning direction rotation 67°.
[0118] (6) In a high-purity argon protective atmosphere with an oxygen content strictly controlled at <100 ppm, the SLM device selectively melts and repeatedly lays powder according to the set path, and finally integrates to form multiple gas diffusion layer samples with FCC imitation lattice structure. The overall size of the sample is 18 mm x 5 mm x 3 mm and 20 mm x 20 mm x 20 mm.
[0119] 4. Post-processing stage
[0120] (1) The FCC lattice GDL 18 mm x 5 mm x 0.5 mm sample was cut and taken from the SLM forming substrate.
[0121] (2) The 4# parameter combination in Table 2 was selected for heat treatment: heat treatment temperature 900 °C, heating rate 5 °C min -1 , holding time 6 hours, then slowly cooled to below 300 °C at a rate of 2 °C min -1 , and finally cooled to room temperature in the furnace.
[0122] 5. Performance characterization and test results
[0123] (1) Residual stress: The surface residual stress of SLM state is 195 MPa (tensile stress) measured by XRD method, and it is reduced to 32 MPa (tensile stress) after heat treatment, with a decrease of 83.6%. This result shows that the heat treatment system at 900℃ is extremely effective for eliminating the high residual stress generated during the SLM forming process. The extremely low residual stress level (32 MPa) means that the GDL has extremely high dimensional stability and stress corrosion resistance during subsequent processing and long-term service, solving the risk of deformation or early cracking of SLM components due to internal stress.
[0124] (2) The prepared GDL structure (sample size is 20mm x 20mm x 20mm) was subjected to compression mechanical property evaluation, and the specific steps are as follows:
[0125] The heat-treated lattice-imitated GDL structure was subjected to quasi-static uniaxial compression test (strain rate 1 x 10 -4 s -1 ) on a universal testing machine. The structure showed excellent mechanical properties, with a compression yield strength of 810 MPa and a compression strength of 1202 MPa, and did not collapse until a strain of 32%, as shown in Figure 4(b). The structure, while maintaining high strength, exhibits excellent plasticity and energy absorption capacity, which is due to the inherent high symmetry of the FCC lattice, which makes it exhibit better ductility than the BCC structure when under load. This characteristic ensures that the GDL can well adapt to the stress fluctuations and potential impact during the assembly and operation of the electrolytic cell, effectively avoiding the brittle fracture or crushing that easily occurs in traditional rigid porous materials, thereby meeting the stringent requirements of the electrolytic cell for mechanical stability.
[0126] (3) Electrolytic water performance: The SLM printed alloy block after the above treatment was made into a sample with a sample size of 18mm x 5mm x 0.5mm. In order to build a high specific surface area nanoporous structure on the surface to further improve the catalytic activity, the sample was subjected to electrochemical dealloying treatment, the principle of which is to selectively corrode the active metal elements (such as Al) in the alloy, thereby leaving a three-dimensional double-continuous nanoporous skeleton rich in transition metals (Fe, Co, Cr, Ni). Double electrodes were used for electrochemical dealloying, working electrode: test sample; counter electrode: carbon rod; dealloying solution: 0.5mol L -1 of sulfuric acid (H2SO4). Software CHI760e was used, with the following parameters set: constant voltage 4V for electrochemical dealloying, and dealloying time 60 minutes. The morphology after dealloying is shown in Figure 3(b). In a 1.0M KOH electrolyte, a standard three-electrode system was used for testing.
[0127] 1) Hydrogen evolution reaction performance:
[0128] a. Polarization curve: As shown in FIG. 6(a), the overpotential (η -2 ) measured at 50 mA cm 50 -2 was 143 mV, which was much lower than the target of the application (≤ 150 mV).
[0129] b. Tafel slope: As shown in FIG. 6(b), the Tafel slope was 164.3 mV dec -1 , indicating that the HER reaction kinetics was rapid.
[0130] c. Stability: As shown in FIG. 6(c), after continuous electrolysis at a constant current density of 50 mA cm -2 -2 for 120 hours, the activity decay rate was about 4.5%, showing excellent long-term stability.
[0131] 2) Oxygen evolution reaction performance:
[0132] a. Polarization curve: As shown in FIG. 6(d), the overpotential (η -2 ) measured at 50 mA cm 50 -2 was 271 mV, which was better than the target of the application (≤ 300 mV).
[0133] b. Tafel slope: As shown in FIG. 6(e), the Tafel slope was 61.2 mV dec -1 , indicating that the OER reaction kinetics was excellent.
[0134] c. Stability: As shown in FIG. 6(f), after continuous operation at a large current density of 50 mA cm -2 -2 for 120 hours, the activity decay rate was about 3.3%, meeting the stability requirement.
[0135] The embodiment is directed to high-performance electrolytic cells that pursue high mass transfer efficiency and reaction kinetics. By using a face-centered cubic (FCC) lattice (rod diameter 200 μm), the highly symmetrical unit structure forms a three-dimensional mass transfer channel with excellent through-put and low detour; combined with high temperature heat treatment at 900°C, it promotes the full diffusion of elements and the formation of balanced stable phases, laying an ideal foundation for subsequent dealloying to prepare a high-activity catalytic surface layer. The extremely low OER overpotential (271 mV) and the smallest OER Tafel slope (61.2 mV / dec) directly solve the core bottleneck of the sharp rise of the mass transfer overpotential caused by bubble blockage and limited electrolyte diffusion inside the electrode when running at high current density, and are particularly suitable for improving the energy conversion efficiency of the electrolytic cell in the full load range.
[0136] The preparation method of the eutectic high-entropy alloy-based gas diffusion layer for the AEMWE electrolytic cell provided by the embodiment of the application comprises the following steps:
[0137] 1. Preparation of metal powder
[0138] (1) Select block high-purity metal raw materials Al, Fe, Co, Cr and Ni with a purity of not less than 99.95%, and accurately weigh them according to the atomic ratio Al:Fe:Co:Cr:Ni = 1:1:1:1:2.1.
[0139] (2) Put the weighed metal raw materials into a beaker containing alcohol, and place them in an ultrasonic cleaning machine for cleaning for 15 minutes to remove surface grease and oxides, and then dry them in a 80℃ vacuum drying box for 2 hours.
[0140] (3) Put the cleaned and dried raw materials into the graphite crucible of the vacuum induction melting furnace. The melting chamber is vacuumed to 5×10 -3 Pa, and then high-purity argon (purity 99.999%) is filled to -0.05 MPa. The vacuuming-argon filling process is repeated 3 times to ensure that the oxygen content in the furnace is lower than 10 -2 Pa. Then, melting is carried out, and the melting temperature is controlled at 1600℃ (about 200℃ higher than the estimated liquidus of the alloy), and the composition is uniformly maintained for 10 minutes by electromagnetic stirring. In order to obtain a highly uniform alloy ingot, the above melting process is repeated 5 times.
[0141] (4) Spherical alloy powder is prepared by high-pressure gas atomization. After remelting the alloy ingot, the molten metal liquid is guided to the atomizing nozzle through the flow guide pipe, and is broken and atomized into fine droplets under the action of 6 MPa ultra-high pressure argon gas flow.
[0142] (5) The atomized powder is cooled in an inert atmosphere protection collection tank. Then, the powder is sieved in an argon-protected glove box using a standard vibrating sieve machine, and the powder with a particle size of 15-53 μm is selected for SLM printing.
[0143] (6) The sieved powder is characterized: scanning electron microscope (SEM) observation shows that the powder is regular spherical, and there are few satellite balls; the average particle size (D50) measured by a laser particle size analyzer is 38 μm; the flow time measured by a Hall flowmeter is 55 s / 50 g, showing good flowability; the energy spectrum analysis (EDS) result shows that the content of each element is basically consistent with the designed composition AlFeCoCrNi 2.1 .
[0144] 2. Lattice-like superstructure design and modeling
[0145] A three-dimensional model of a bionic porous structure based on a body-centered cubic (BCC) and face-centered cubic (FCC) cross composite was established using computer-aided design software. The key geometric parameters were set as follows: lattice rod diameter 400 pm, unit size 2 mm x 2 mm x 2 mm, and theoretical porosity 75%. The three-dimensional model was exported as an STL file, and a preliminary prototype was verified using a resin material by light-curing 3D printing technology to confirm the feasibility and accuracy of the structure design, as shown in FIG. 2(c).
[0146] 3. SLM printing forming
[0147] (1) The BCC / FCC composite imitation lattice STL model designed above was imported into the processing software of an SLM device (for example, EOS M290).
[0148] (2) The model was placed in the forming cabin along the Z-axis direction to minimize the support structure and ensure the success rate of printing. The software automatically generated the necessary support.
[0149] (3) The model was sliced, and the layer thickness was set to 20 pm.
[0150] (4) A sandblasted 304 stainless steel substrate was selected and preheated to 110°C. The recovered AlFeCoCrNi 2.1 alloy powder described above was used as the raw material, and a 20 pm thick powder layer was laid on the substrate.
[0151] (5) The 2# parameter combination in Table 1 was selected as the optimized process: laser power 120 W, scanning speed 850 mm / s -1 , scanning pitch 0.07 mm, layer thickness 30 pm, and adjacent layer laser scanning direction rotation 67°.
[0152] (6) In a high-purity argon protective atmosphere with an oxygen content strictly controlled at <100 ppm, the SLM device selectively melted and repeatedly laid powder according to the set path, and finally integrated and formed multiple gas diffusion layer samples with a BCC / FCC composite imitation lattice structure. The overall size of the sample was 18 mm x 5 mm x 3 mm and 20 mm x 20 mm x 20 mm.
[0153] 4. Post-processing stage
[0154] (1) The imitation lattice GDL 18 mm x 5 mm x 0.5 mm sample was cut and removed from the SLM forming substrate.
[0155] (2) The 5# parameter combination in Table 2 was selected for heat treatment: heat treatment temperature 1000°C, heating rate 5°C / min -1 , holding time 4 hours, and then 2°C / min -1The temperature was slowly decreased to 300°C, and then the furnace was cooled to room temperature.
[0156] 5. Performance characterization and test results
[0157] (1) Residual stress: The residual stress of the SLM state surface was measured by XRD method to be 210 MPa (tensile stress), which was reduced to 18 MPa (tensile stress) after heat treatment, with a decrease of 91.4%.
[0158] (2) The prepared GDL structure (sample size of 20 mm x 20 mm x 20 mm) was subjected to compression mechanical property evaluation, and the specific steps were as follows:
[0159] The heat-treated lattice-imitated GDL structure was subjected to quasi-static uniaxial compression test (strain rate of 1 x 10 -4 s -1 ) on a universal testing machine. The structure showed excellent mechanical properties, with a compression yield strength of 1903 MPa and a compression strength of 2983 MPa, and did not collapse until a strain of 22% was reached, as shown in Figure 4 (c), showing good plasticity and energy absorption capacity. The mechanical properties far exceeded conventional porous metals or carbon-based GDLs, and were sufficient to meet the extremely high compression and deformation resistance requirements of space-limited electrolytic cells for electrode components.
[0160] (3) Water electrolysis performance: The SLM printed alloy block after the above post-treatment was made into a sample with a sample size of 18 mm x 5 mm x 0.5 mm. In order to build a high specific surface area nano-porous structure on the surface to further improve the catalytic activity, the sample was subjected to electrochemical dealloying treatment, the principle of which is to selectively corrode the active metal elements (such as Al) in the alloy, thereby leaving a three-dimensional double-continuous nano-porous skeleton rich in transition metals (Fe, Co, Cr, Ni). Double electrodes were used for electrochemical dealloying, working electrode: test sample; counter electrode: carbon rod; dealloying solution: 0.5 mol L -1 of sulfuric acid (H2SO4). Software CHI760e was used, and the parameters were set as follows: constant voltage 4V for electrochemical dealloying, and dealloying time 60 minutes. The morphology after dealloying is shown in Figure 3 (c). In a 1.0M KOH electrolyte, a standard three-electrode system was used for testing.
[0161] 1) Hydrogen evolution reaction performance:
[0162] a. Polarization curve: As shown in Figure 7 (a), the overpotential (η -2 ) was measured to be 76 mV at a current density of 50 mA cm 50 , which was much lower than the target of the invention (≤150 mV).
[0163] b. Tafel slope of 142.6 mV dec-1 As shown in Figure 7(b), it indicates that its HER reaction kinetics is rapid.
[0164] c. Stability: As shown in Figure 7(c), it shows excellent long-term stability under harsh working conditions after continuous electrolysis for 120 hours at a constant current density of 50 mA cm -2
[0165] 2) Oxygen evolution reaction performance:
[0166] a. Polarization curve: As shown in Figure 7(d), the overpotential (η -2 ) measured at 50 mA cm 50 current density is 253 mV, which is better than the invention target (≤ 300 mV).
[0167] b. Tafel slope is 98.3 mV dec -1 As shown in Figure 7(e), it indicates that its OER reaction kinetics is excellent.
[0168] c. Stability: As shown in Figure 7(f), the activity decay rate is about 2.2% after continuous operation for 120 hours at a large current density of 50 mA cm -2 , further proving its durability as an integrated electrode under dynamic load.
[0169] This embodiment is aimed at extreme working conditions and space-limited scenarios with strict requirements for volume power density, such as vehicle-mounted and ship-mounted hydrogen production equipment. By adopting a BCC and FCC cross-combined simulated lattice, a "truss-in-truss" type super-strong mechanical design is realized. This design disperses the load path in multiple directions, greatly improving the specific strength and specific stiffness of the structure, successfully solving the core contradiction that traditional electrodes cannot be thinned due to insufficient strength, leading to the inability to improve the volume power density in extremely compact electrolytic cell stack designs, allowing the electrode to maintain structural integrity when subjected to ultra-high in-plane pressure tightness; and using ultra-high temperature heat treatment of 1000°C, the purpose is not only to almost completely eliminate residual stress (decrease 91.4%), but more importantly to drive alloy elements to fully diffuse, achieving the ultimate uniformity and stability of the organization. This solves the long-term durability problem that the microstructure of the material may evolve due to metastability under harsh conditions such as long-term, vibration, and thermal cycling, which in turn leads to degradation of catalytic performance or decline in structural reliability. Most importantly, while achieving such ultra-high strength, it still maintains the lowest HER overpotential (76 mV), which proves that this scheme can break the traditional dilemma of "strength and activity" and provide an unprecedented material and structural integrated solution for the design of high-power density electrolytic cells.
[0170] The preparation method of the eutectic high-entropy alloy-based gas diffusion layer for the AEMWE electrolytic cell provided by the embodiment of the application comprises the following steps:
[0171] 1. Preparation of metal powder
[0172] (1) Select block high-purity metal raw materials Al, Fe, Co, Cr, Ni with a purity of not less than 99.95%, and accurately weigh them according to the atomic ratio Al:Fe:Co:Cr:Ni = 1:1:1:1:2.1.
[0173] (2) Put the weighed metal raw materials into a beaker containing alcohol, and place them in an ultrasonic cleaning machine for cleaning for 15 minutes to remove surface grease and oxides, and then dry them in a 80℃ vacuum drying box for 2 hours.
[0174] (3) Put the cleaned and dried raw materials into the graphite crucible of the vacuum induction melting furnace. The melting chamber is vacuumed to 5×10 -3 Pa, and then high-purity argon (purity 99.999%) is filled to -0.05 MPa. The vacuuming-argon filling process is repeated 3 times to ensure that the oxygen content in the furnace is lower than 10 -2 Pa. Then, melting is carried out, and the melting temperature is controlled at 1600℃ (about 200℃ higher than the estimated liquidus of the alloy), and the composition is uniformly maintained for 10 minutes by electromagnetic stirring. In order to obtain a highly uniform alloy ingot, the above melting process is repeated 5 times.
[0175] (4) Spherical alloy powder is prepared by high-pressure gas atomization. After remelting the alloy ingot, the molten metal liquid is guided to the atomizing nozzle through the flow guide pipe, and is broken and atomized into fine droplets under the action of 6 MPa ultra-high pressure argon gas flow.
[0176] (5) The atomized powder is cooled in an inert atmosphere protection collection tank. Then, the powder is sieved in an argon-protected glove box using a standard vibrating sieve machine, and the powder with a particle size of 15-53 μm is selected for SLM printing.
[0177] (6) The sieved powder is characterized: scanning electron microscope (SEM) observation shows that the powder is regular spherical, with few satellite balls; the average particle size (D50) measured by a laser particle size analyzer is 38 μm; the flow time measured by a Hall flowmeter is 55 s / 50 g, showing good flowability; the energy spectrum analysis (EDS) result shows that the content of each element is basically consistent with the designed composition AlFeCoCrNi 2.1 .
[0178] 2. Lattice-like superstructure design and modeling
[0179] A porous structure model based on horizontal intersection of face-centered cubic (FCC) and body-centered cubic (BCC) lattices was established using computer-aided design software. The key geometric parameters were set as follows: the lattice rod diameter gradually changed from 150 pm at the bottom to 450 pm at the top, the unit size was 1.8 mm x 1.8 mm x 1.8 mm, and the theoretical porosity was 55%. The three-dimensional model was exported as an STL file, and a preliminary prototype verification was performed using resin material by light-curing 3D printing technology to confirm the feasibility and accuracy of the structure design, as shown in FIG. 2(d).
[0180] 3. SLM printing forming
[0181] (1) The gradient BCC imitation lattice STL model designed above was imported into the processing software of the SLM equipment (for example, EOS M290).
[0182] (2) The model was placed in the forming cabin along the Z-axis direction to minimize the support structure and ensure the success rate of printing. The software automatically generated the necessary support.
[0183] (3) The model was sliced, and the layer thickness was set to 50 pm.
[0184] (4) A sandblasted 304 stainless steel substrate was selected and preheated to 80°C. The recovered AlFeCoCrNi 2.1 alloy powder described above was used as the raw material, and a 50 pm thick powder layer was laid on the substrate.
[0185] (5) The 7# parameter combination in Table 1 was selected as the optimized process: laser power 250 W, scanning speed 800 mm / s -1 , scanning pitch 0.1 mm, layer thickness 30 pm, and adjacent layer laser scanning direction rotation 90°.
[0186] (6) In a high-purity argon protective atmosphere with oxygen content strictly controlled at <100 ppm, the SLM equipment selectively melts and repeatedly lays powder according to the set path, and finally integrates multiple gas diffusion layer samples with gradient BCC imitation lattice structure. The overall size of the sample is 18 mm x 5 mm x 3 mm and 20 mm x 20 mm x 20 mm.
[0187] 4. Post-processing stage
[0188] (1) The imitation lattice GDL 18 mm x 5 mm x 0.5 mm sample was cut and taken from the SLM forming substrate;
[0189] (2) The 1# parameter combination in Table 2 was selected for heat treatment: heat treatment temperature 600°C, heating rate 5°C / min -1 , holding time 4 hours, and then 2°C / min -1The temperature was slowly decreased to 300°C, and then the furnace was cooled to room temperature.
[0190] 5. Performance characterization and test results
[0191] (1) Residual stress: The surface residual stress of SLM state was 175 MPa (tensile stress) measured by XRD method, and decreased to 45 MPa (tensile stress) after heat treatment, with a decrease of 74.3%.
[0192] (2) The prepared GDL structure (sample size of 20 mm x 20 mm x 20 mm) was subjected to compression mechanical property evaluation, and the specific steps were as follows:
[0193] The heat-treated lattice-imitated GDL structure was subjected to quasi-static uniaxial compression test (strain rate of 1 x 10 -4 s -1 ) on a universal testing machine. The structure showed excellent mechanical properties, with a compression yield strength of 1174 MPa and a compression strength of 1865 MPa. It did not collapse until a strain of 28% was reached, as shown in Figure 4 (d), showing good plasticity and energy absorption capacity, sufficient to meet the fastening requirements during electrolytic cell assembly and the mechanical stability during long-term operation.
[0194] (3) Electrolytic water performance:
[0195] The SLM printed alloy block after the above post-treatment was made into a sample with a sample size of 18 mm x 5 mm x 0.5 mm. In order to build a high specific surface area nanoporous structure on the surface to further improve the catalytic activity, the sample was subjected to electrochemical dealloying treatment. The principle is to selectively corrode the active metal elements (such as Al) in the alloy, leaving a three-dimensional bi-continuous nanoporous skeleton rich in transition metals (Fe, Co, Cr, Ni). A double electrode was used for electrochemical dealloying, with the working electrode being the test sample, the counter electrode being a carbon rod, and the dealloying solution being 0.5 mol L -1 of sulfuric acid (H2SO4). The software CHI760e was used, and the parameters were set as follows: constant voltage 4V for electrochemical dealloying, and dealloying time 60 minutes. The morphology after dealloying is shown in Figure 3 (d). In a 1.0M KOH electrolyte, a standard three-electrode system was used for testing.
[0196] 1) Hydrogen evolution reaction performance:
[0197] a. Polarization curve: As shown in Figure 8 (a), the overpotential (η -2 ) at a current density of 50 mA cm 50 was 126 mV, which was much lower than the target of the invention (≤150 mV).
[0198] b. Tafel slope of 114.3 mV dec -1 As shown in Figure 8(b), it indicates that the HER reaction kinetics is fast.
[0199] c. Stability: As shown in Figure 8(c), the activity decay rate is about 3.0% after continuous electrolysis at a constant current density of 50 mA cm -2 for 120 hours, which shows excellent long-term stability. This stability verifies its durability under the simulated renewable energy fluctuation input working condition.
[0200] 2) Oxygen evolution reaction performance:
[0201] a. Polarization curve: As shown in Figure 8(d), the overpotential (η -2 ) measured at 50 mA cm 50 current density is 263 mV, which is better than the target of the application (≤ 300 mV).
[0202] b. Tafel slope of 104.1 mV dec -1 As shown in Figure 8(e), it indicates that the OER reaction kinetics is excellent.
[0203] c. Stability: As shown in Figure 8(f), the activity decay rate is about 2.3% after continuous operation at a large current density of 50 mA cm -2 for 120 hours, which meets the stability requirement. This indicates that the electrode structure can effectively resist the damage caused by reverse polarity, potential sudden change and other factors caused by power fluctuation.
[0204] The embodiment is aimed at the gas-liquid transfer management problem faced by electrolytic cells directly coupled with fluctuating renewable energy sources such as wind power and photovoltaic power under dynamic and variable load conditions. By designing a gradient BCC lattice structure, the pore structure from the catalyst layer-membrane interface (bottom) to the flow channel side (top) is precisely controlled: the 150 μm thin rod diameter at the bottom forms a dense area to maximize the electrochemical active area and optimize current collection, and the 450 μm thick rod diameter at the top forms an open area to provide a low-resistance channel for the rapid nucleation, confluence and escape of reaction gas (H2 / O2), which solves the two failure modes of "flooding" (active sites covered by electrolyte at low current) and "drying" (gas blockage hindering electrolyte replenishment) that are prone to occur in traditional homogeneous pore electrodes when the current density frequently changes. At the same time, a 600°C low-temperature heat treatment strategy is adopted to effectively relax most of the residual stress (decrease by 74.3%) while ensuring the dimensional stability of the component, and at the same time, the unique non-equilibrium fine-grained structure and high-density crystal defects of SLM ultrafast solidification are intentionally retained as high-activity catalyst sites, which not only ensures the high intrinsic catalytic activity of the electrode under dynamic conditions, but also prevents the initiation of microcracks in frequent thermal cycling through moderate stress relief, perfectly solving the balance problem between catalytic activity and structural durability. Finally, the synergistic application of the above technical features makes the GDL of the embodiment exhibit excellent working condition adaptability and rapid response capability: excellent HER reaction kinetics (Tafel slope of 114.3 mV / dec) ensures that hydrogen can be produced efficiently and quickly when the power of renewable energy sources suddenly increases, and the optimal gas-liquid management capability brought by the gradient pore structure ensures the stable operation of the electrode in a wide range of current densities, providing core electrode technical support for building an efficient, robust and long-life green hydrogen production system seamlessly connected with intermittent renewable energy sources.
[0205] To clearly compare and demonstrate the comprehensive performance of the application, the key data of the compression mechanical properties and water electrolysis catalytic properties of the four embodiments are summarized in Table 3 and Table 4, respectively.
[0206] Table 3: Summary of compression mechanical properties of the four embodiments
[0207] Table 4: Summary of electrochemical properties of the four embodiments
[0208] As can be seen from the data in Table 3 and Table 4, although the four embodiments differ in the design of the crystal lattice structure and the SLM and heat treatment process parameters, the EHEA-GDL prepared by them all exhibits excellent comprehensive performance.
[0209] Firstly, in terms of mechanical properties (see Table 3), the compressive yield strength of all samples is between 800 MPa and 2000 MPa, the compressive strength is higher than 1200 MPa, and the highest can reach 2983 MPa, while maintaining a plastic strain rate of 22% to 32%. This indicates that the GDL prepared by the application has extremely high structural stability, which is sufficient to withstand the physical stress in the electrolytic cell assembly pressure and long-term operation, solving the problem of easy collapse and peeling of traditional porous electrodes or catalytic coatings.
[0210] Secondly, in terms of electrochemical catalytic performance (see Table 4), all implementation cases have achieved the invention goal in hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Among them, the 50mA cm -2 The HER overpotential (η 50 ) under current density is between 76mV and 143mV, which is much better than the design requirement of ≤150mV; the OER overpotential (η 50 ) is between 253mV and 279mV, which is significantly better than the design requirement of ≤300mV. The corresponding Tafel slope is also at a low level (HER: 114.3-164.3mV dec -1 ; OER: 61.2-104.1mV dec -1 ), which proves the fast catalytic reaction kinetics. More importantly, the activity decay rate of all samples is less than 5% after 120 hours of continuous operation at a current density of 10mA cm -2 .
[0211] Comprehensive analysis shows that the application successfully prepares an EHEA catalytic electrode with low residual stress, unique microstructure and excellent water electrolysis catalytic performance (low overpotential, small Tafel slope and high stability) by specific component design (AlFeCoCrNi 2.1 ), optimized SLM preparation process parameter range, subsequent heat treatment system and flexible spatial structure design. The application first applies SLM additive manufacturing technology to the integrated forming of high-entropy alloy catalytic electrodes with multi-level pore structure, solving the problems of high interface impedance between the catalytic layer and the diffusion layer in traditional electrodes, poor mechanical stability and limited mass transfer, etc. It provides a new technical route for the preparation of high-performance and long-life AEMWE electrolytic cells, and has good industrial application prospects.
[0212] To further prove the positive effects of the above examples, the application based on the above technical solutions carries out the following experiments.
[0213] Firstly, at the material design level, the application realizes the breakthrough of intrinsic performance of catalytic materials through the eutectic high-entropy alloy (EHEA) system. Traditional non-noble metal catalysts generally face the dilemma of difficult to balance activity and stability: single transition metal has limited activity and is easy to dissolve, while conventional multi-element alloy is easy to cause element segregation and phase separation, resulting in activity decay. The EHEA composition AlFeCoCrNi2.1 used in the application utilizes its unique high-entropy effect, lattice distortion effect and slow diffusion effect to fundamentally inhibit the precipitation of harmful phases and promote the synergistic catalytic effect between elements. More importantly, its unique dual-phase eutectic structure provides an ideal precursor for subsequent electrochemical dealloying treatment, which can in-situ construct a three-dimensional nanoporous catalytic skeleton with high specific surface area and excellent stability, thereby solving the core contradiction between low cost and high performance, high stability of non-noble metal catalysts at the material source.
[0214] Secondly, at the structure manufacturing level, the application realizes the integrated design and manufacturing of "material-structure-function" through selective laser melting (SLM) technology, which completely revolutionizes the construction mode of traditional electrodes. The existing technology generally adopts a step-by-step process of "preparing diffusion layer first, then coating catalyst", which inevitably introduces problems such as interface impedance between the catalytic layer and the substrate, weak bonding force, and thermal expansion mismatch. The application creatively utilizes SLM technology to directly form EHEA materials with catalytic potential into a three-dimensional porous structure with precise programming of the simulated lattice (GDL). This integrated manufacturing mode not only eliminates the physical interface, realizes seamless and efficient transmission of electrons / mass transfer, but also integrates the catalytic active sites with the macroscopic conductive and mass transfer skeleton, making the mechanical bonding strength equivalent to the bulk material, which fundamentally solves the problems of easy falling off of the catalytic layer, large interface resistance and interface failure under long-term operation.
[0215] Finally, in terms of performance and applicability, the present application exhibits excellent comprehensive performance and wide scene adaptability through flexible "component-process-structure" synergistic regulation. As shown in various embodiments and data in Tables 3 and 4, the mechanical strength (yield strength 810-1903 MPa) of the EHEA-GDL series products prepared by the present application is far superior to traditional carbon-based or sintered metal GDL, completely solving the problems of assembly crushing and long-term mechanical failure; the catalytic activity (HER overpotential 76-143 mV, OER overpotential 253-279 mV) and stability (120-hour decay rate <5%) are comparable to or even better than the noble metal benchmark. More importantly, by optimizing the structure (such as BCC, FCC, composite, gradient lattice) and post-processing process (such as 800-1000°C heat treatment) respectively, the present application can directionally prepare special electrodes suitable for different application scenarios such as industrial-grade high robustness, high-efficiency mass transfer, ultra-high power density and dynamic working conditions, providing unprecedented customization capability, and providing a solid material and device foundation for the diversified and high-performance development of AEMWE electrolytic cell technology.
[0216] The above merely describes preferred specific embodiments of the present application, but the protection scope of the present application is not limited thereto, and any modification, equivalent replacement and improvement made by those skilled in the art within the technical range disclosed by the present application, as long as it is within the spirit and principle of the present application, shall be covered within the protection scope of the present application.
Claims
1. A method for preparing a eutectic high-entropy alloy-based gas diffusion layer for an AEMWE electrolyzer, characterized in that, The method The method comprises the following steps: S1, prepared by gas atomization method, has the composition AlFeCoCrNi. 2.1 Eutectic high-entropy alloy spherical powder; S2, a model with a three-dimensional quasi-lattice superstructure is established under optimized parameters by an SLM process; S3, a gas diffusion layer component is integrally formed from the eutectic high-entropy alloy spherical powder according to the model under a protective atmosphere by using a selective laser melting technology; S4, the gas diffusion layer component is subjected to heat treatment, and then the gas diffusion layer component is subjected to electrochemical dealloying treatment in an acidic solution to form a three-dimensional bicontinuous nano-porous structure on the surface.
2. The method of preparing eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolyzer according to claim 1, characterized in that, In step S1, the preparation of the eutectic high-entropy alloy spherical powder comprises: After the metal raw materials with an atomic ratio of Al:Fe:Co:Cr:Ni = 1:1:1:1:2.1 are weighed, cleaned by alcohol ultrasonic cleaning and dried, surface contaminants are removed; The pretreated metal raw materials are placed in a vacuum induction melting furnace for vacuum induction melting, the melting temperature is controlled at 150-300 DEG C above the liquidus of the alloy, and the melting is repeated 4-6 times; The spherical alloy powder is prepared by a high-pressure gas atomization method under an argon atmosphere of 2-8 MPa, and the eutectic high-entropy alloy spherical powder with a particle size of 15-53 μm is obtained by screening.
3. The method of making eutectic high-entropy alloy-based gas diffusion layers for AEMWE electrolyzers of claim 2, wherein, Before vacuum induction melting of the metal raw material, the oxygen content in the furnace is reduced to 10 -2 Pa or below by vacuum-purge cycle treatment with argon.
4. The method of making eutectic high-entropy alloy-based gas diffusion layers for AEMWE electrolyzers of claim 1, wherein, In step S2, the quasi-lattice superstructure adopts a face-centered cubic, body-centered cubic or multi-phase inlaid composite form, the rod diameter is 100-500 μm, and the porosity is 50-80%.
5. The method of claim 1, wherein the eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolyzers is prepared by the steps of: In step S3, the eutectic high-entropy alloy spherical powder is integrally formed into a gas diffusion layer component according to the model, comprising: A CAD software is used to design a three-dimensional model of the quasi-lattice structure and convert it into a standard triangulation language file; According to the Z-axis height, surface roughness and minimum support structure requirements, the best manufacturing direction is adjusted, and the support structure is generated; The model file is sliced into equal-thickness layers according to the set thickness, and the slicing data is transmitted to the SLM device; The 304 stainless steel substrate is preheated, the preheating temperature is controlled at 80-120 DEG C, and then a layer of metal with a thickness of 20-50 μm is uniformly laid on the preheated substrate; A high-energy density laser beam selectively melts the metal powder in the x-y plane according to the path planning data; The powder laying scraper lays another layer of metal powder on the completed layer, and the laser beam selectively melts according to the slicing data of the next layer, and the powder laying is repeated until the gas diffusion layer component is obtained.
6. The method of claim 5, wherein the eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolyzers is prepared by the steps of: The substrate preheating temperature is 80-120 DEG C, the powder laying thickness is 20-50 μm, and the protective atmosphere is argon with an oxygen content of less than 100 ppm; The process parameters of the selective laser melting technology range from 100-350 W of laser power, 600-1000 mm / s of scanning speed, 0.06-0.1 mm of scanning pitch, and 20-60 μm of layer thickness; The overall size of the gas diffusion layer component is 18 mm x 5 mm x 3 mm and 20 mm x 20 mm x 20 mm.
7. The method of making eutectic high-entropy alloy-based gas diffusion layers for AEMWE electrolyzers of claim 1, wherein, In step S4, the heat treatment is carried out under vacuum, the temperature is raised to 600-1100 DEG C at a rate of 5 DEG C / min, and the temperature is maintained for 1-6 h; after the holding is completed, the temperature is lowered to below 300 DEG C at a rate of 2 DEG C / min, and the furnace is cooled to room temperature. The electrochemical dealloying treatment adopts a double electrode, a constant voltage of 4V is applied in a 0.5mol / L sulfuric acid solution for 60min.
8. A eutectic high-entropy alloy-based gas diffusion layer for an AEMWE electrolyzer, characterized in that, The gas diffusion layer is made by the preparation method of the eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolytic cell according to any one of claims 1 to 7, and the material of the gas diffusion layer is AlFeCoCrNi 2.1 The eutectic high-entropy alloy has a three-dimensional eutectic lattice macro-pore structure and a three-dimensional double-continuous nano-porous structure covering the surface of the macro-structure skeleton.
9. The eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolyzers of claim 8, wherein, In a 1.0M KOH electrolyte, at least one of the following performance indicators is met: hydrogen evolution reaction at 50 mA cm -2 overpotential at a current density of 50 mA cm is ≤ 150 mV; The oxygen evolution reaction at 50 mA cm -2 overpotential at 50 mA cm -300 mV. The Tafel slopes of the hydrogen evolution reaction and the oxygen evolution reaction are less than 180mV / dec and 110mV / dec, respectively; at 50 mA cm -2 The activity decay rates of both hydrogen evolution reaction and oxygen evolution reaction are not more than 5% after continuous operation for 120 h at 50 mA cm 10. The eutectic high-entropy alloy-based gas diffusion layer for AEMWE electrolyzers of claim 8, wherein, It has a multi-level pore structure, and the compressive yield strength is 800-2000MPa, the compressive strength is 1000-3200MPa, and the strain rate is 20-35%.
Citation Information
Patent Citations
AlCoCrFeNi2.1 eutectic high-entropy alloy and selective laser additive manufacturing preparation method thereof
CN113210629A
Laser additive manufactured AlCoCrFeNi2 eutectic high-entropy alloy and strengthening method thereof
CN114686718A
Preparation method of water electrolysis device
CN115011985A
Method for preparing high-entropy alloy by combining direct-writing 3D printing and hot isostatic pressing technology
CN117961084A
FeCoNiAlTi high-entropy alloy with lattice truss structure and preparation method of FeCoNiAlTi high-entropy alloy
CN118404094A